(untitled) (Bangladesh Journal of Medical Science, 2024)
Background: The most common cause of death among children is pediatric pneumonia. The increase of antibiotic abuse to treat pediatric pneumonia patients in Bangladesh is alarming for the rise of multidrug-resistant (MDR) bacteria. However, there is a dearth of research available regarding this. Hence, the current study was conducted on a pilot scale to identify the MDR bacteria from pediatric pneumonia patients by molecular approaches. Methods: Saliva and nasal swab samples were collected for 3 months (July- September 2019) from 3children with suspected pneumonia at two different hospitals in Jashore city, Bangladesh. Routine biochemical tests were performed to identify the isolates presumptively. All isolates were tested for antimicrobial resistance according to CLSI guidelines using 17 antibiotics. Finally, amplified ribosomal DNA restriction analysis (ARDRA) and 16S rRNA sequencing with phylogeny were performed to confirm the bacteria at the species level. Results: From the samples collected from the patients, 47 isolates were obtained. The biochemical tests presumptively identified Acinetobacter spp., as the most prevalent type, which was followed by Staphylococcus spp., and Enterobacter spp. Surprisingly, every isolate was MDR, resistant to at least four antibiotics. Cefepime and Cefotaxime showed the highest (i.e., 100% and 87%, respectively) resistance pattern. In addition, the isolates showed elevated resistance towards Amoxicillin, Vancomycin, Streptomycin, Azithromycin, Erythromycin, Norfloxacin, and Tetracycline. On the contrary, they were susceptible to Imipenem and Meropenem. Subsequently, the isolates were typed into three different groups by ARDRA; the strains Acinetobacter baumannii, Enterobacter hormaechei, and Staphylococcus pasteuri were confirmed. Conclusion: The rapid revolution of multidrug resistant organisms has an impact on morbidity, mortality and healthcare associated cost. Unrestricted use of antibiotics should be stopped and surveillance is necessary for controlling the emergence of resistant bacteria Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 729-738